Going with the flow: employee flow experiences across the creative profession spectrum - Lizerbram, Ryan S., author; Fisher, Gwen, advisor; Dik, Bryan, committee member; Rhodes, Matthew, committee member; Beer, Laura, committee member (Colorado State University. Libraries, 2024)
Ties between the psychological state of flow and creativity, as well as flow and occupational health, have been documented relatively well within the organizational psychological literature, but fewer studies attempt to bridge these relationships together in a single study, especially when considering the lens of work design. In this study, I sought to test a model comprising work design, creative processes, flow experiences, and occupational health variables to empirically examine whether creative problem-solving and work-related flow mediate the relationship between job characteristics and worker well-being. I conducted an online self-report survey among a convenience sample of 326 workers employed in a variety of occupations. In general, the results provided support for the hypothesized model. Results indicated that job characteristics relate to creative problem-solving, flow, and worker well-being, which can inform ways to possibly increase flow at work. This research contributes to the broader literature that has previously identified numerous benefits of work-related flow, such as positive mood, overall well-being, in-role job performance, organizational citizenship behaviors, work recovery, and depleted burnout.
Keywords: flow; occupational health; worker well-being; job characteristics; creative process; work design